(untitled) (JURNAL GEOCELEBES, 2022)
Mining activities require large work areas that potentially cause environmental problems. One of the impacts that can be caused is an increase of erosion rate, which can reduce the function of the land, especially in the location that planned to be mine rehabilitation area. The potential for erosion formed must be predicted to prepare methods of prevention. Estimation of erosion potential was carried out at Tiung AB Dump PT. Kaltim Prima Coal uses the RUSLE (Revised Unified Soil Loss Equation) method which considers rain erosivity, material erodibility, slope factor, vegetation factor and conservation factor. Based on the results of the study, the average erosion rate was 292.4 tons/ha/month with a catchment area of ​​0.674 km2. Erosion reduction uses a conservation technique using the terracing method which is supported by the construction of an open channel to drain the rain discharge that enters the catchment area. Rainfall uses data from the last 15 years with the highest rainfall in January of 231.9 mm/month and the lowest in September of 118.3 mm/month. The 10-year return period of the highest rainfall is 121.49 mm/day. Peak runoff rainfall is 13.22 m3/s with infiltration discharge is 9.72 m3/s. The designed open channel has a flow rate of 21.09 m3/s with supercritical flow. The use of a tire drop structure can reduce the speed up to 3.8 m/s which is within the permissible speed based on the type of material so that erosion can be reduced to 11.7 tons/ha/month or 96% of the natural erosion rate.